THE USE OF LEXICAL UNITS REPRESENTING THE RELATIONSHIP LEVEL OF A PERSON IN THE WORK OF "MAHBUB UL-QULUB". - Raimov Akbar (Social science and innovation, 2023)
In this article, detailed information is given and analyzed about the use of lexical units representing the level of kinship of a person in the Mahbub ul Qulub epic of Alisher Navoi, the Sultan of the word property